Cumulative exposure to poor housing affordability and its association with mental health in men and women. Issue 9 (11th November 2011) - Bentley, Rebecca; Baker, Emma; Mason, Kate
Abstract : Background: Poor housing affordability affects around 10% of the Australian population and is increasingly prevalent. The authors tested two hypotheses: that cumulative exposure to housing affordability stress (HAS) is associated with poorer mental health and that effects vary by gender. Methods: The authors estimated the relationship between cumulative exposure to HAS and mental health among 15 478 participants in an Australian longitudinal survey between 2001 and 2009. Individuals were classified as being in HAS if household income was in the lowest 40% of the national distribution and housing costs exceeded 30% of income. Exposure to HAS ranged from 1 to 8 annual waves. Mental health was measured using the Short Form 36 Mental Component Summary (MCS) score. To test the extent to which any observed associations were explained by compositional factors, random- and fixed-effects models were estimated. Results: In the random-effects models, mental health scores decreased with increasing cumulative exposure to HAS (up until 4+ years). This relationship differed by gender, with a stronger dose-response observed among men. The mean MCS score of men experiencing four to eight waves of housing stress was 2.02 points lower than men not in HAS (95% CI −3.89 to −0.16). In the fixed-effects models, there was no evidence of a cumulative effect of HAS on mental health; however, lower MCS was observed after a single year in HAS (β=−0.70, 95% CI −1.02 to −0.37). Conclusions: While average mental health was lower for individuals with longer exposure to HAS, the mental health effect appears to be due to compositional factors. Furthermore, men and women appear to experience cumulative HAS differently.